Peningkatan Alokasi Anggaran Militer Negara-Negara di Timur Tengah dan Pengaruhnya terhadap Eskalasi Konflik Kawasan - Endro Tri Susdarwono (Indonesia Center for Middle East Studies, 2021)
This study aims to discuss how military budget allocations for countries in the Middle East affect the escalation of conflicts in the region, how military budget allocations must compete between countries in the area, and how military budget allocations have a relationship and influence with each other. This study uses quantitative methods, namely statistical tests with canonical correlation analysis, to answer the relationship and impact between military budget allocations among countries in the Middle East. The results of canonical weight and canonical loading functions 1 and 2 show a significant relationship between the dependent variate and the independent variate or military budget allocation in Iran, Israel, Saudi Arabia, and Turkey and military budget allocations in seven other countries in the Middle East. The existence of competition in the distribution of military budgets in Middle Eastern countries affects the escalation of conflicts in this region because the preparation of the budget is based on threats. The funding for defense is a concern and consideration for friendly or unfriendly neighboring countries.